2023
DOI: 10.1186/s13046-023-02665-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ERα-dependent breast cancer metastasis by a miR-29a signaling

Abstract: Malignant breast cancer (BC) remains incurable mainly due to the cancer cell metastasis, which is mostly related to the status of Estrogen receptor alpha (ERα). However, our understanding of the mechanisms through which ERα regulates cancer cell metastasis remains limited. Here we identified a miR-29a-PTEN-AKT axis as a downstream signaling pathway of ERα governing breast cancer progression and metastasis. Two estrogen response element (ERE) half sites were identified in the promoter and enhancer regions of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 51 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…In bladder, prostate, and various gastrointestinal tumor tissues, miR-29a is found to be significantly downregulated, and its low expression plays a pro-oncogenic role [42][43][44]. However, in cholangiocarcinoma and breast cancer, miR-29a demonstrates upregulation, promoting tumor development [45,46]. In HCC, Liu et al found that miR-29a expression is reduced and promotes tumor proliferation by negatively regulating the expression of IFITM3 [47].…”
Section: Discussionmentioning
confidence: 99%
“…In bladder, prostate, and various gastrointestinal tumor tissues, miR-29a is found to be significantly downregulated, and its low expression plays a pro-oncogenic role [42][43][44]. However, in cholangiocarcinoma and breast cancer, miR-29a demonstrates upregulation, promoting tumor development [45,46]. In HCC, Liu et al found that miR-29a expression is reduced and promotes tumor proliferation by negatively regulating the expression of IFITM3 [47].…”
Section: Discussionmentioning
confidence: 99%